Analisis Kepuasan Konsumen di PT. Royal Bestindo Shakti - Raga Aquino; Eka Febrianata; Heri Sapari Kahpi (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to explore the influence of product quality and brand image on consumer satisfaction levels. The explanatory research approach, with data obtained by distributing questionnaires. The sampling technique uses the Slovin formula, a sample of 94 respondents. The method is carried out quantitatively. Based on descriptive analysis, information is obtained regarding product quality and brand image in relation to consumer satisfaction. Partial tests show that product quality and brand image have a positive and significant influence on consumer satisfaction. In addition, the results of the simultaneous test inform that there is a positive and significant influence of both variables on consumer satisfaction.